El estudio de la disgrafía para la corrección de la escritura con las niñas y los niños de cuarto grado, de la escuela de educación básica Municipal Héroes del Cenepa, del barrio Esteban Godoy, de la parroquia San Sebastián, de la ciudad de Loja, periodo lectivo 2013 - 2014 - Diaz Collaguazo, Jessenia Veronica (2015)
The present research work titled: THE DYSGRAPHIA STUDY OF THE FOR THE CORRECTION OF THE HANDWRITING WITH THE GIRLS AND CHILDREN OF FOURTH GRADE OF DE SCHOOL EDUCATION BASIC MUNICIPAL HEROES OF THE CENEPA, OF THE BARRIO ESTEBAN GODOY, PARISH SAN SEBASTIAN, OF CITY OF LOJA, PERIOD LECTIVO 2013-2014, had as general objective: To contribute with this work to the enrichment and improvement of the quality of basic general education, through the study of dysgraphia to achieve a correct writing in fourth grade students of the School of Basic Education Municipal Heroes Cenepa, develop, implement and evaluate the effectiveness of the practical answer key for the timely treatment of dysgraphia for the correct spelling in the fourth graders. It was developed with the use of the following methods: scientist, analytic, synthetic, participatory diagnosis, model or proactive, comprehensive workshop and assessment and valuation; techniques as the poll with his respective questionnaire instrument were applied to eight students, four teachers and eight parents respectively. For the analysis and representation of the results were used statistical tables. It is concluded that the application of a practical answer key to overcome dysgraphia by the researcher through workshops, directly benefited the students, helping to reduce their disgráficas difficulties demonstrated through the Pearson r.